2017
DOI: 10.1515/congeo-2017-0011
|View full text |Cite
|
Sign up to set email alerts
|

Computation of precise geoid model of Auvergne using current UNB Stokes-Helmert’s approach

Abstract: Abstract:The aim of this paper is to show a present state-of-the-art precise gravimetric geoid determination using the UNB Stokes-Helmert's technique in a simple schematic way. A detailed description of a practical application of this technique in the Auvergne test area is also provided. In this paper, we discuss the most problematic parts of the solution: correct application of topographic and atmospheric effects including the lateral topographical density variations, downward continuation of gravity anomalie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…As one can see, a correction for lateral topographical density variations was not included in the computation because a density model was not available at the time of the computation. Also, the Hörmander effect has not been included, but is very small compared to our expected final centimetric accuracy (see Janák et al (2017)). Fig.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…As one can see, a correction for lateral topographical density variations was not included in the computation because a density model was not available at the time of the computation. Also, the Hörmander effect has not been included, but is very small compared to our expected final centimetric accuracy (see Janák et al (2017)). Fig.…”
Section: Resultsmentioning
confidence: 92%
“…In addition to the main steps described so far in this document, a geoid computation involves numerous small details, which can lead to an incorrect result if neglected (see Janák et al (2017)). Thus, to perform the computation, the researcher must thoroughly study the technique.…”
Section: The Process Of Geoid Computationmentioning
confidence: 99%
“…These debates, while important, are not closely related to our thesis, so we will not refute them in detail. However, we do take issue with Popadyev reiterating the historical arguments for the Molodensky system while he, and any reviewers of his paper, have ignored the massive body of work showing that they are no longer valid (Vaníček and Martinec 1994;Martinec and Vaníček 1994;Vaníček et al 1999;Huang et al 2001;Janák and Vaníček 2001;Tenzer et al 2003;Tenzer and Vaníček 2003;Tenzer et al 2005;Kingdon et al 2005;Santos et al 2006;Cheraghi et al 2007;Kingdon et al 2012;Foroughi and Tenzer 2017;Foroughi et al 2017a, b;Janák et al 2017;Goli et al 2018;Foroughi 2018;Foroughi et al 2019;Sheng et al 2019;Vaníček and Santos 2019;Goli et al 2019a, b)-the references indicated come mostly from geodesists who follow the "University of New Brunswick's (UNB) line of thought" (as this is a rebuttal paper) but it is by no means complete, as many other colleagues dedicated to the classical theory validate our assumptions. Among other things, this substantial list of references shows that several quantities Popadyev claims are "unknown" or "unknowable" can be determined with sufficient accuracy.…”
Section: Auxiliary Argumentsmentioning
confidence: 97%
“…Nowadays, the external accuracy of regional geoid models (e.g., by comparison with geometrical geoid heights, determined at sites observed by both Global Navigation Satellite Systems (GNSS) and spirit leveling) is typically on the level of a few centimeters (e.g., Denker 2013; Szelachowska and Kryński 2014;Bucha et al 2016;Ågren et al 2016;Gerlach and Ophaug 2017;Janák et al 2017), with a few sub-cm exceptions (e.g., Ellmann et al 2019;Foroughi et al 2019;Slobbe et al 2019). On this level, however, it is not a trivial task to differentiate between the errors from each contributing element (geoid, GNSS, leveling).…”
Section: Introductionmentioning
confidence: 99%